2015
DOI: 10.1016/j.sleh.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of insufficient sleep across the United States: a county-level hotspot analysis

Abstract: Introduction Insufficient sleep is associated with cardiometabolic risk and neurocognitive impairment. Determinants of insufficient sleep include many social and environmental factors. Assessment of geographic hot/coldspots may uncover novel risk groups and/or targets for public health intervention. The aim of this study was to discern geographic patterns in the first data set to include county-level sleep data. Methods The 2009 Behavioral Risk Factor Surveillance System was used. Insufficient sleep was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Using county-level data from the 2009 Behavioral Risk Factor Surveillance System (BRFSS), Grandner et al identified insufficient sleep ‘hotspots’ in the Appalachian region that connects Tennessee, Virginia, West Virginia, Kentucky, and Ohio. Similar hotspots were found in the Midwest and southeast United States(11). …”
Section: Habitual Sleep Duration and Cardiovascular Diseasesupporting
confidence: 76%
“…Using county-level data from the 2009 Behavioral Risk Factor Surveillance System (BRFSS), Grandner et al identified insufficient sleep ‘hotspots’ in the Appalachian region that connects Tennessee, Virginia, West Virginia, Kentucky, and Ohio. Similar hotspots were found in the Midwest and southeast United States(11). …”
Section: Habitual Sleep Duration and Cardiovascular Diseasesupporting
confidence: 76%
“…At the regional level, recent studies have shown that geography explains sleep disturbance [84] and insufficient sleep [149] in the United States. Specifically, a state-by-state analysis by Grandner and colleagues [84] examined 36 US states to show that those in southern states were more likely to report difficulty sleeping over the past two weeks.…”
Section: Unpacking Race/ethnicity Findingsmentioning
confidence: 99%
“…12,13 This study identified the following factors negatively influencing postmenopausal women's quality of sleep: smoking, number of hot flashes, and age of menopause. However, it is not possible to identify causality, because this was a cross-sectional study, not interventionist.…”
Section: Discussionmentioning
confidence: 99%